Rancang Bangun Alat Sterilisator UV Ruangan Berbasis IoT Di RSUD Blambangan - Ratna Mustika Yasi; M.Najib Fikri Fadillah; Charis Fathul Hadi (ZETROEM, 2022)
The purpose of the IoT-based uv sterilizer design that uses the NODEMCU ESP32 as a microcontroller is to utilize digitalization technology that can be used to help the medical team at Blambangan Hospital in terms of room UV sterilization, because the hospital still uses manual control. UV rays have a very dangerous radiation effect if exposed to humans directly, so it is necessary to design a control device that can help the medical team avoid UV radiation. In this study using NODEMCU as a data receiver that has been integrated into the UV sterilizer user room network and uses an application on android as a remote control.